Causes of Open Defecation in East Java Province in 2018 - Hadi, Shalikul; Megatsari, Hario (Universitas Airlangga, 2022)
Background: Open defecation (OD) is a sanitation problem that can have a negative impact on health. Open defecation can have a bad impact on sanitation this poor sanitation can then trigger various diseases. Objective: This study aims to find out the factors related to the behavior of open defecation (OD) in Regency/City communities of East Java Province in 2018. Methods: Ecological approach based on secondary data published by the Ministry of Health of the Republic of Indonesia, East Java Provincial Health Office, and the Central Statistics Agency of East Java Province of 38 districts/cities in East Java Province were included in this study. This study examined the percentage of healthy latrine users with 4 other independent variables, namely the percentage of facilities that met the available requirements, the percentage of villages that applied Community Led Total Sanitation (CLTS), the prevalence of diarrhea cases, and the percentage of illiteracy rates. Data were analyzed using cross tabulation with SPSS. Results: There were still several districts/cities in East Java Province that had not used latrines when defecating, most of them were in districts/cities with inadequate facilities, low percentage of villages willing to implement CLTS, low percentage of illiteracy, and moderate diarrhea prevalence. Conclusion: Based on these results, it can be concluded that the factors of the availability of facilities, education, compliance with CLTS implementation, and the prevalence of diarrhea have a relationship with the percentage of latrine users in districts/cities in East Java Province. The results of this study can be used by local stakeholders to make health-based policies as an effort to reduce open defecation.